Pengaruh Media Sosial Dan Persepsi Publik Terhadap Keputusan Penggunaan Make Up Artist (Studi Kasus Di Yogyakarta) The Influence of Social Media and Public Perception on Decisions to Use Make Up Artists (Case Study in Yogyakarta) - Purba, Cindy Agawati; Triana, Dewi; Widiyanti, Anik; Melati, Sunti (EBBANK, 2024)
This study aims to determine the influence of social media and public perception on the decision to use makeup artists. This type of research is quantitative descriptive, this study uses a descriptive approach, and the sampling technique is Purposive sampling. The study was conducted by collecting questionnaires. The population in the study was domiciled in Yogyakarta, the selected respondents had criteria, namely, women aged 18>52 years, had used makeup artists, had seen advertisements and promotions carried out by service providers and social media. with a sample of 100 respondents. Analytical methods in multiple linear regression test research, classical assumption test and hypothesis test. The results showed that partially social media variables and public perception had a significant effect on the decision to use makeup artists. And likewise simultaneously (together) the variables of social media variables and public perception have a significant influence on the decision to use makeup artists.